Pengembangan Media Pembelajaran Berbasis Moodle pada Mata Kuliah Fisika Dasar - Lovy Herayanti; M. Fuaddunnazmi; Habibi Habibi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The purpose of this study was to fundamental develop a Moodle-based learning media and know how to influence the use of instructional media on physics course. This research includes the development of research conducted through three stages that is: preliminary studies, design development, and testing media. Subjects of the study were students at the FPMIPA IKIP Mataram which was following the fundamental Physics course. Moodle-based learning media development in fundamental physics courses have been designed and have done the settings on the story board and page navigation, profile settings, administration settings, and management course settings. Devices and media that have been developed and then validated and tested on a limited scale.